2018
DOI: 10.1093/femsyr/foy017
|View full text |Cite
|
Sign up to set email alerts
|

An expanded enzyme toolbox for production of cis, cis-muconic acid and other shikimate pathway derivatives in Saccharomyces cerevisiae

Abstract: A wide range of commercially relevant aromatic chemicals can be synthesized via the shikimic acid pathway. Thus, this pathway has been the target of diverse metabolic engineering strategies. In the present work, an optimized yeast strain for production of the shikimic acid pathway intermediate 3-dehydroshikimate (3-DHS) was generated, which is a precursor for the production of the valuable compounds cis, cis-muconic acid (CCM) and gallic acid (GA). Production of CCM requires the overexpression of the heterolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 51 publications
1
81
0
1
Order By: Relevance
“…The shikimate pathway has received major attention in recent years by serving as a source of aromatic scaffolds for the production of fine and commodity chemicals, including aromatic amino acids, dopamine, naringenin, p-coumaric acid, resveratrol, vanillin, and MA (3)(4)(5)(6)(7)(8)(9)(10). While Escherichia coli has been engineered to produce up to 36.8 g/liter MA (11), brewer's yeast (Saccharomyces cerevisiae) is often regarded as the superior MA production host because fermentations can be carried out at a low pH to facilitate downstream processing.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The shikimate pathway has received major attention in recent years by serving as a source of aromatic scaffolds for the production of fine and commodity chemicals, including aromatic amino acids, dopamine, naringenin, p-coumaric acid, resveratrol, vanillin, and MA (3)(4)(5)(6)(7)(8)(9)(10). While Escherichia coli has been engineered to produce up to 36.8 g/liter MA (11), brewer's yeast (Saccharomyces cerevisiae) is often regarded as the superior MA production host because fermentations can be carried out at a low pH to facilitate downstream processing.…”
mentioning
confidence: 99%
“…The strain, harboring DHS dehydratase (AroZ), protocatechuic acid (PCA) decarboxylase (AroY), and catechol dioxygenase (CatA), produced only 1.56 mg/liter of MA. Since this initial demonstration, a number of studies have reported iterative improvements in the yield and titer of heterologous DHSderived products (4,8,(13)(14)(15)(16). From these efforts, it is evident that yeast MA production suffers from two major challenges: (i) achieving high performance of the heterologous pathway for efficient conversion of DHS to MA and (ii) balancing carbon flux between the shikimate pathway and the heterologous branch.…”
mentioning
confidence: 99%
See 3 more Smart Citations